Faster intervals, faster recoveries - intensified short VO2max running intervals are inferior to traditional long intervals in terms of time spent above 90% VO2max - Daniel Fleckenstein; Hannes Braunstein; Nico Walter (Frontiers in Sports and Active Living)
IntroductionHigh intensity interval training for improving maximal oxygen consumption (VO2max) is a fundamental component of specific preparation phases for middle- and long-distance runners. In this context, short intervals are very popular in practice. The aim of the present study was to determine whether increasing the intensity of short intervals around maximal aerobic speed (vVO2max), compared to traditional long interval runs, leads to a greater time spent above 90% VO2max.Methods12 highly trained middle distance runners (7 males, 5 females) completed two VO2max sessions (4 × 3 min at 95% vVO2max, recovery: 3 min at 50% vVO2max vs. 24 × 30 s at 100% vVO2max, recovery: 30 s at 55% vVO2max) on the treadmill in randomized order. Spiroergometric data, lactate accumulation, heart rate (HR) and perceived exertion was determined. This allowed the recording of time above 90% VO2max and time above 90% HRmax. To analyze differences between the interval sessions, the paired t-test respectively the Wilcoxon test, if data were not normally distributed, were applied.ResultsThe time spent above 90% VO2max was significantly lower in the 30-s intervals, despite the higher intensity, compared to the 3-min session (201.3 ± 268.4 s vs. 327.9 ± 146.8 s, p = 0.05, r = 0.57). In contrast, the time spent above 90% HRmax was significantly higher for the 30-s intervals than for the 3-min intervals (820 ± 249 s vs. 545 ± 131 s, p < 0.001, d = 1.73). The blood lactate concentrations showed higher values in the 3-min session (9.69 ± 1.82 mmol/L) compared to the 30-s session (7.59 ± 2.01 mmol/L, p < 0.001, d = 2.34). There was no statistical difference in the rating of perceived exertion between the two sessions (30-s session: 6.5 ± 1.0 vs. 3-min session: 6.8 ± 1.2; p = 0.26).DiscussionThe present study showed that intensified 30-s intervals were inferior to traditional 3-min intervals regarding the time spent above 90% VO2max. Given the observation of an opposing trend in the time spent above 90% HRmax, this parameter should be interpreted with caution in traditional training settings.